2008
DOI: 10.1109/lpt.2007.911007
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for an All-Optical Flip-Flop Using a Single Distributed Feedback Laser Diode

Abstract: Abstract-We introduce a new concept for an all-optical flip-flop based on a single distributed feedback laser. The injection of external light into the laser results in a nonuniform carrier distribution. We will show numerically that this nonlinear effect of the carriers gives rise to a bistability that can be exploited for fast flip-flop operation.Index Terms-All-optical flip-flops, distributed feedback (DFB) lasers, optical bistability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…The reset-pulses are combined with a holding beam (1546 nm) of approximately 3 dBm to make the DFB laser operative in the bistable regime. The set-pulses are injected at the opposite side of the laser to restore the uniformity of the carriers [5]. The output of the DFB AOFF is sent to an SOA-based MZI which converts the optical packet to the wavelength of the AOFF (1553 nm).…”
Section: Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The reset-pulses are combined with a holding beam (1546 nm) of approximately 3 dBm to make the DFB laser operative in the bistable regime. The set-pulses are injected at the opposite side of the laser to restore the uniformity of the carriers [5]. The output of the DFB AOFF is sent to an SOA-based MZI which converts the optical packet to the wavelength of the AOFF (1553 nm).…”
Section: Conceptmentioning
confidence: 99%
“…Recently, we demonstrated that a single antireflection-coated distributed-feedback (DFB) laser with a -shift operates as a fast AOFF under the injection of continuous-wave light [5], [6]. DFB lasers are already widely used in today's telecommunication industry and the added functionality as optical memory element offers, therefore, an economically viable way to achieve all-optical packet switching.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some work has recently been presented on optical random access memories (RAM) [4], [5], which could open new directions in all-optical networking. A digital optical memory, implemented via an all-optical flip-flop (AOFF), can be used to store an optical bit with almost infinite duration [6]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…Digital Object Identifier 10.1109/JQE.2014.2378376 The AOFF based on an anti-reflection-coated (AR-coated) λ/4-shifted distributed feedback (DFB) laser diode, which has been already experimentally demonstrated [14], [15], has the main advantage that it can operate over a broad wavelength range for the set and reset pulses and that it is based on mature device technology. It requires externally injected light, but there are no hard wavelength requirements for the external beam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation